Diseño de una estrategia preventiva en la anorexia en adolescentes basada en la evidencia científica - Tapuy Licuy, Lisbeth Katherine (2025)
Anorexia is a group of eating disorders, which is considered a psychiatric illness with a high rate of mortality due to this pathology. Objective: The aim of this study was to design a preventive strategy for anorexia in adolescents, based on scientific evidence through an exhaustive review of the literature. Methodology: The methodology used in this investigation was a literature review with a qualitative approach. The search strategy was based on the use of keywords to enter digital search engines such as Pubmed, Science Direct, Dialnet and Google Scholar to obtain the appropriate information, applying the PRISMA methodology to obtain the most relevant studies that meet the selection criteria. Results: One of the strategies with the greatest impact was the education provided by nursing staff as prevention in primary care. The most well - known treatments are: family treatment, inpatient treatment and outpatient treatment, thus it is also observed that it is relevant that nursing intervention should focus on education not only of the patient but also of the caregiver or parents. Conclusions: It has been evidenced that within the treatments, it is important to carry out preventive talks to avoid the complications that anorexia generates in the health of adolescents, by means of practical programme guides focused on education about healthy habits, the promotion of a positive body image and the promotion of coping skills.